(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the changes of MAC, Et-Desfluran, Fi-Desfluran in Desfluran anesthesia under the guidance of Bispectral index for kidney transplantation from living donors. Subjects and methods: 50 patients scheduled for kidney transplantation from living donors under endotracheal anesthesia, and control anesthesia concentration by Et-Control with Desfluran achieved BIS within the range of 40-60. Assess changes in MAC, Fi-Desfluran, Et-Desfluran, heart rate, mean blood pressure, CVP, SpO2 at the time points after 15 minutes of intubation, skin incision, iliac artery clamping, 10 minutes after reperfusion, skin closure and amount of anesthetic consumed, recovery time, extubation time and some side effects after anesthesia. Results: The highest MAC, Fi-Desfluran, Et-Desfluran values at the time of skin incision were 0.67 ± 0.13; 5.3 ± 0.8%; 5.2 ± 0.9% respectively, the lowest at 10 minutes after reperfusion, respectively 0.44 ± 0.12; 3.1 ± 0.4%; 2.7 ± 0.5%, the average Desfluran anesthetic volume was 13.1 ± 2,1 ml/hour, average recovery time is 5.65 ± 2.4 minutes, average extubation time is 8.7 ± 2.6 minutes. Conclusion: During anesthesia for kidney transplantation from living donors, parameters include: MAC, Fi-Desfluran, Et-Desfluran, BIS is highest at the time of skin incision, lowest at the time after 10 minutes of reperfusion, the average volume of Desfluran anesthetic used was 13.1 ± 2.1 ml/hour, recovery time was 5.65 ± 2.4 minutes, extubation time was 8.7 ± 2.6 minutes.